Strategi Perlindungan Hukum Merek UMKM di Yogyakarta Melalui Peraturan Gubernur DIY No 21 Tahun 2017 Tentang Penggunaan Merek Jogjamark, 100%Jogja dan Jogjatradition sebagai Co Branding Produk Daerah (Lex Jurnalica, 2023)
The presence of SMEs as creative industries in Yogyakarta is quite a lot but there is still a small management of creative results in the field of Intellectual Property Rights. The problem in this study, first is how the role of the Yogyakarta Regional Government in providing IPR registration facilities for SMEs, secondly how the Regional Government provides IPR service facilities for SMEs in the Industrial 4.0 era. This research is a normative juridical research. The primary data of this study are the results of direct field research. The results of this study are the first that in Yogyakarta there are regulations for SMEs in order to protect their products, namely Governor Regulation No. 21 of 2017 Regarding the Use of the Jogja Mark Brand, 100% Jogja and Jogja Tradition as Co-Branding of Regional Products, by the Intellectual Property Management Center of the Special Province of Yogyakarta. Both websites are currently being developed that can be used to provide IPR services, namely